Improving PSM and HSEMS compliance in Malaysian upstream oil and gas industry: a case study assessment for plug and abandonment activities - Zulkiply, Mohd Shazman; Hussain, Siti Aslina (Wiley, 2023)
Process safety incidents in the oil and gas industry can have serious consequences. In the United States and Malaysia, standards for process safety management (PSM) have been established by US OSHA and PETRONAS, respectively. However, these standards are not always properly understood or followed by employers, resulting in ineffective safety programs and uncontrolled hazards. Plug and abandonment (P&A) activities in the upstream oil and gas industry require high control of well barriers. To assess the gap between PSM industrial standards and crew awareness in P&A activities, a study was conducted throughout one cycle of the project campaign. The study found that 70% of offshore crews had a high awareness level of the health, safety, and environment management system (HSEMS) and PSM, and 96% compliance was achieved from audit activities. However, two proposed PSM elements scored low in the assessment, indicating a need for improvement in site implementation. The study provides valuable information for offshore crews and readers seeking to improve and assess PSM elements in process safety. The results can help identify and control potential hazards related to technical safety, operational safety, and personnel safety. Furthermore, the study aims to support the development and implementation of PSM standards in Malaysia.